'Harder than other lessons but good': the effect of colleague collaboration on secondary English pupil engagement. (1st October 2020) - Collyer, Edward; Lawrence, Clare; Jacobs, Lisa; Mitchell, Rosa; Fox Goddard, Paul
ABSTRACT: Research examining collaborative planning in British secondary schools relates primarily to the effect it has on a teacher's professional development. Researchers seldom focus on the impact on pupils. This study was designed to understand the effect collaboratively planned lessons had on pupil engagement in a British secondary school. Transcripts from lessons observations, reflective diaries and field notes were analysed using thematic analysis. One theme was identified: 'Pupils' Engagement with Differentiated Instruction'. This research concludes that collaboratively planned lessons allowed some pupils to engage in learning better than individually planned lessons. The professional learning occurring from the planning process allowed teachers to collaboratively plan a lesson that was stronger than an individually planned lesson. This is significant as the UK's Independent Teacher Workload Review Group promotes collaborative planning as a method of reducing workload. However, collaborative planning is only worth doing if evidence implies that it improves pupil outcomes.